Construction Waste Audit in the Framework of Sustainable Waste Management in Construction Projects—Case Study - Spišáková, Marcela; Mésároš, Peter; Mandičák, Tomáš (Buildings (Basel), 2021)
The issue of sustainability has long been the subject of interest in architecture engineering and the construction sector. All three aspects of sustainability—economic, environmental, and social—can be affected through appropriate construction waste management. Construction and demolition waste (CDW) is one of the largest worldwide waste streams, therefore, it is given great attention by all stakeholders (investors, contractors, authorities, etc.). Research studies show that one of the main barriers to insufficient CDW recovery is inadequate policies and legal frameworks to manage CDW. It is also one of European Union’s (EU) environmental priorities. The aim of the article was to confirm the economic potential of construction and demolition waste audit processing through a case study. A pre-demolition waste audit was processed for an unused shopping center building in the town Snina in Slovakia. Subsequently, a comparison of economic parameters (waste disposal costs and transport costs) of the recommended CDW management was performed. This comparison confirmed the economic benefits of environmentally friendly construction waste management methods according to the waste audit results, which would also increase the sustainability of construction projects. Additionally, the cost parameters of selected waste disposal methods could be another dimension of building information modeling.